Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1007/bf02266961
|View full text |Cite
|
Sign up to set email alerts
|

Identification of major components of larviposition pheromone from larvae of tsetse fliesGlossina morsitans morsitans Westwood andGlossina morsitans centralis Machado

Abstract: The presence of pheromones produced by larvae ofGlossina morsitans morsitans andG. m. centralis, respectively, which attract gravid females and result in aggregation of pupae, is confirmed. Behavioral experiments indicated that females preferred to larviposit over moist sand conditioned by previously allowing larvae to pupariate in it. Similar results were obtained with filter papers contaminated with the prepupariation excretions of larvae and with volatiles collected from larvae prior to pupariation.n-Pentad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…Previous studies have suggested that the moistening of the deposition substrate can lead to increases in larval deposition rates in tsetse (Saini et al, 1996). The moisture content of the deposition substrate was increased by sprinkling 100 ml of water over the sand in each tray in the artificial burrows.…”
Section: Burrow Modificationsmentioning
confidence: 99%
“…Previous studies have suggested that the moistening of the deposition substrate can lead to increases in larval deposition rates in tsetse (Saini et al, 1996). The moisture content of the deposition substrate was increased by sprinkling 100 ml of water over the sand in each tray in the artificial burrows.…”
Section: Burrow Modificationsmentioning
confidence: 99%
“…These technologies are environment friendly [4], and applicable for riverine and savanna species of tsetse flies [5], [6]. The attractants include various phenolic derivatives [7][9], carbon dioxide, acetone, 1-octen-3-ol, and vertebrate host breath, skin and urine extracts [10][12]. Interestingly, 1-octen-3-ol is a constituent of the chemical profile from Lantana camara , an invasive plant to which tsetse flies are attracted [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, riverine tsetse species (such as G. fuscipes fuscipes , G. palpalis and G. tachinoides ) prefer feeding on reptilian hosts compared to their savanna relatives ( G. morsitans morsitans , G. pallidipes ) that feed largely on ungulates and other large mammals [6]. Larvipostion pheromones (n-pentadecane and n-dodecane) from exudates of mature larvae are also known to attract and induce gravid G. m. morsitans and G. m. centralis females to aggregate and deposit larvae [23]. Research on response to tastants in tsetse flies are limited, but point to their potential application in tsetse control [10], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation pheromones, which specifically attract gravid females to lay their eggs in batches within larger egg masses at single sites, have thus far been described only from haematophagous Diptera (McCall & Cameron, 1995). Such oviposition aggregation pheromones have been found in culicine mosquitoes (Laurence & Pickett, 1985) and phlebotomine sandflies (El Naiem & Ward, 1991;Dougherty et al, 1994), and active components of a pheromone eliciting larval aggregation have been identified in the viviparous tsetse (Glossinidae; Saini et al, 1996). Within the Simuliidae, a number of species other than S. daiwiosnm s.l.…”
Section: Introductionmentioning
confidence: 99%